Structure, Strategy and Organizational Design in Albanian Context - Shkurti, Ludmilla (European Journal of Multidisciplinary Studies, 2016)
This research paper will try to understand and explain how much and how is understood the nature, the importance and factors that affect the business organizational structure and design in Albanian Organizations, compared with theoretical factors researched from the literature. How a business does structure in our country, knowing how important are the theoretical factors in business organization performance and therefore how much and how the principles of organizational design are applied in Albanian Organizations. Why structure, strategy and organizational design? Organizational design and organizational restructuring remains one of the most important issues that management of organizations, in the global era and information technology, must deal with, for the fact that businesses today face some unprecedented challenges: increased competition, globalization, growing of social responsibility, technological changes, changes in taste and consumer’s exigency, new strategic thinking, etc. Referring the literature and contemporary researchers, a constant topic during these recent years has been the one of how globalization and economic crisis have obliged the organizations to review their strategies and to change the way they operate, trying often therefore to structure for surviving and achieving success. These challenges should be carefully managed in order to build and hold a high performance organization, to deal with tough competition and endless problem that this era we live does bear. It is also important to understand correctly that organizational structure and design, by dictating roles connection in an organization and consequently how people function, may often be the main cause of the problems, but also one more reason of success. The way that organizations structure or the specific model of business, may constitute their competitive advantage, or special strategic skills, so it can make a business organization unique and competitive in the market. For many researchers the prevailing conclusion is that the organizations either neglect the importance of organizational design, or they just do not know what to do about it and therefore they evolve in an indirectly, spontaneous or intuitive way. From what the paper identifies, most of organizational structuring in Albania are made in a hasty way, without seeing or paying attention to full frame or circumstances. This may result in some partial and fragmentary initiatives instead of aiming in organizational designing and general structuring. This is not surprising as the subject is complex, often poorly explained and not rightly understood even though the academics and the consulters have made a great work to address the organizational design topic. However the paper shows that entrepreneurs and managers still lack a practical and systematic framework in order to guide their choices of organizational structure. To find a practical approach for the organizational design, can be difficult, even though some business schools have tried to simplify the things. The study will try to achieve this task, through careful research, in order to diagnose the organizational design process and restructuring situation in Albania, highlighting the effect of the current challenges which have an impact on this difficult process, mainly based on a survey of 200 organizational businesses in Albania.